ANALISIS PRODUKSI USAHA AMPLANG DI DESA TABANIO KABUPATEN TANAH LAUT - FITRIA AUDINA; MUHAMMAD RUSMIN NURYADIN (PPJP Universitas Lambung Mangkurat, 2019)
Fitria Audina (2019), Analysis of Amplang Production in Tabanio Village, Tanah Laut Regency. Advisor: M.Rusmin Nuryadin, SE, M.Si.This study was conducted to (1) analyze what factors influence the amount of production in the Amplang business in Tabanio Village, Tanah Laut Regency; (2) analyze the scale of the amplang roduction business in Tabanio village, Tanah Laut Regency; and (3) analyzing the level of efficiency of the amplang production business in Tabanio Village, Tanah Laut Regency. By using the Cobb-Douglas model.The results of this study indicate that simultaneous production factors (main raw material 1, main raw material 2, supporting raw materials 1, supporting raw materials 2 and labor wages have no significant effect. The results of the envelope production scale in Tabanio Village, Tanah Laut Regency are decreasing return ti scale with a production elasticity of 0,936. While the efficiency of input use is the main raw material 2 and supporting raw material 1 is still inefficient, while the efficiency of raw material input main 1, supporting raw material 2 and labor wages are inefficient. Keywords : Factor of Production, Return To Scale, Marginal Product Value